Differentiable self-consistent space-charge simulation for accelerator design - Ji Qiang (Physical Review Accelerators and Beams, 2023)
The nonlinear space-charge effects in a high intensity or high brightness accelerator can have a significant impact on the beam properties through the accelerator. These effects are included in the accelerator design via self-consistent multiparticle tracking simulations. In order to study the sensitivity of the final beam’s properties with respect to the accelerator design parameters, one has to carry out the time-consuming space-charge simulation multiple times. In this paper, we propose a differentiable self-consistent space-charge simulation model that enables the study of such sensitivity through only one simulation. This model differs from previous applications of the truncated power series algebra by connecting the beam properties directly with the accelerator design parameters in the presence of collective space-charge effects so that the local derivative of the beam properties with respect to the design parameters can be computed during the simulation. Such a model can also be used with gradient-based numerical optimizers for accelerator design optimizations including the self-consistent space-charge effects.